2019
DOI: 10.1186/s12886-019-1092-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy of diabetic retinopathy screening by physician graders using a hand-held non-mydriatic retinal camera at a tertiary level medical clinic

Abstract: Background The evidence on diagnostic test accuracy (DTA) of diabetic retinopathy (DR) screening utilising photographic studies by non-ophthalmologist personnel in low and middle-income country (LMIC) settings is scarce. We aimed to assess DTA of DR screening using a nonmydriatic hand-held digital camera by trained general physicians in a non-ophthalmic setting. Methods This study is a validation of a screening intervention. We selected 700 people with diabetes (PwDM) >… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 51 publications
2
34
2
Order By: Relevance
“…For grader 2 (family physician) sensitivity was 92.5% and specificity was 96.4%. 30 This study findings showed slightly better results when compared to our study. This difference could be because of inclusion of only referable DR cases and mydriatic fundus photographs in their study.…”
Section: Discussioncontrasting
confidence: 50%
“…For grader 2 (family physician) sensitivity was 92.5% and specificity was 96.4%. 30 This study findings showed slightly better results when compared to our study. This difference could be because of inclusion of only referable DR cases and mydriatic fundus photographs in their study.…”
Section: Discussioncontrasting
confidence: 50%
“…The distribution of the dataset largely affects the test performance of the computer-aided diagnosis algorithm 26 . Although some studies have demonstrated fair levels of accuracy with a balanced dataset, the low incidence of positive findings in the clinical scenario leads to a low PPV and a large number of false-positive cases 9 , 27 , 28 . Inverse probability was also used to estimate the algorithm behavior with the population distribution 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in India, Sri Lanka, and Pakistan report satisfactory test accuracy for non-ophthalmologist screening [ 6 , 9 , 31 , 32 ]. Using digital fundus photographs and a nonmydriatic approach, “physician graders” in Sri Lanka showed a sensitivity of 88.7% and specificity of 94.9% [ 10 ]. In Pakistan, optometrists showed 72% sensitivity and 86.3% specificity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a lower rate of ungradable images was reported (56/1511, 4.1%) than that reported in similar health facility–based studies in the South Asian context. A technical failure rate of 7.5% was noted in another study in Bangladesh [ 35 ], which rose to 12% in Sri Lanka [ 10 ]. The higher level of gradeability observed in our study is probably a function of the exclusion criteria or the image-taking technique that was employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation